Verpleegkundige beraming van die behoeftes van moeders met voortydse babas - L. Roets (Curationis, 1995)
Premature labour is and remains an actual problem. There will always be mothers that undergo the crisis of having a premature baby. The unique needs of these mothers remains unfulfilled. Possible reasons for this are that the nurse, working in the neonatal intensive care, special care units or in the post natal ward, does not do a complete assessment of the mother. Nurses are set on the physical needs of the mother and baby during hospitalization and pay more attention to these needs than to others. Those needs which are in fact neglected, are those which are so crucial and important, concerning the mother. In this study, it is needs, other than physical needs, which are emphasized.